Effects of combined exposures of microcystin-LR and benzo[a]pyrene on detoxification in the fish liver cell line (PLHC-1) - Bieczynski, Flavia (2025)
This study focuses on the mixture effects of two classes of common aquatic contaminants, microcystin-LR (MCLR) and benzo[a]pyrene (BaP), on detoxification in a fish liver cell line (PLHC-1). Cells were exposed to non-cytotoxic concentrations, either MCLR (0.01, 1 µM), BaP (0.01, 0.1, 1 µM), or mixtures of both chemicals for 1 to 48 h. Functions and regulations of cytochrome P450 1A (CYP1A) and P-glycoprotein (Pgp) were analyzed. In addition, cytotoxicity was analyzed to ensure non-cytotoxic effects of any of the treatments. Exposure to MCLR, BaP individually or in different mixture combinations induced CYP1A enzyme activity and CYP1A mRNA expression with differences between individual and mixed exposures. An antagonistic mixture effect was seen on the induction of CYP1A enzyme activity. The half maximal inhibition concentration of BaP on CYP1A activity was 1.7 µM, implying weak inhibition by BaP. In contrast, MCLR had no inhibitory effect, suggesting that the antagonistic mixture effect is not due to inhibition of the CYP1A enzyme by MCLR. However, a synergistic mixture effect was seen on induction of CYP1A mRNA levels at early exposure times (1 and 3 h). At 6 h or longer exposures times, only the highest BaP concentration tested (1 µM) induced CYP1A mRNA expression. Function and regulation of Pgp were not significantly affected in any of the exposure experiments. Besides, none of tested concentrations or mixtures caused cytotoxicity. This study suggests mixture effects between MCLR and BaP at lower concentrations (maximum 1 µM) on function and regulation of CYP1A in a fish liver cell line, providing new insights into the potential adverse mixture effects between these two different classes of aquatic contaminants.